Antigen presentation of the Oct4 and Sox2 peptides by CD154-activated B lymphocytes enhances the killing effect of cytotoxic T lymphocytes on tumor stem-like cells derived from cisplatin-resistant lung cancer cells - Zhang, Xueyan (J Cancer, 2018)
The present study investigated whether antigen presentation of the Oct4 and Sox2 peptides by CD154-activated B lymphocytes can enhance the killing effect of CD8(+) cytotoxic T lymphocytes (CTLs) on lung stem-like cancer cells (SLCCs). The CTLs were generated using an accelerated co-cultured dendritic cells (DC) (acDC) assay by incubating human peripheral blood mononuclear cells (PBMCs) from non-small-cell lung cancer patients with antigen peptides of Oct4 and Sox2 in the presence of several DC-activating agents. CD154(+) NIH3T3 cells prepared by CD154 lentiviral transfection were used as feeder layer to activate primary B cells (CD19(+)) obtained from PBMCs. Activated B cells were co-cultured with CTLs to present antigen peptides of Oct4 and Sox2. CTLs co-cultured with activated B cells were evaluated for the levels of secreted inflammatory cytokines using ELISA. In addition, the killing effect of the CTLs on SLCCs derived from cisplatin-resistant strain of human lung cancer cell line PC9 was evaluated by flow cytometry using CFSE labeling of the target cells. After the acDC assay, the PBMCs exhibited a significant (p<0.01) increase in the population of CD8(+)/CD3(+) cells, indicating successful preparation of CTLs. The primary B cells cultured on the CD154(+) NIH3T3 feeder layer resulted in significant (p<0.01) increase in the proportions of population expressing CD80, CD86, or HLA-A, indicating successful activation of the B cells. The co-culture of CTLs with CD154-activated B cells presenting the Oct4 and Sox2 peptides caused significant increase in the levels of secretory inflammatory cytokines and exhibited enhanced killing of the SLCCs derived from cisplatin-resistant PC9 cells. Antigen presentation of the Oct4 and Sox2 peptides by CD154-activated B cells can enhance the killing effect of CTLs towards lung SLCCs.